2020
DOI: 10.3390/d12020069
|View full text |Cite
|
Sign up to set email alerts
|

Venomous Snake Abundance Within Snake Species’ Assemblages Worldwide

Abstract: Venomous snakes are among the main sources of mortality for humans in rural regions, especially in tropical countries. In this study, a meta-analysis of quantitative community ecology studies on snake assemblages throughout the world was conducted in order to evaluate variation in the frequency of occurrence of venomous species and venomous individuals by habitat and continent. A bibliographic search was done by consulting “Google Scholar” and “ISI Web of Knowledge”. In total, 24,200 results were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Snakebite incidence varies on a geographical and temporal scale, resulting from the interaction of anthropic ( Harrison et al, 2009 ; Mise et al, 2016 ) and environmental ( Chaves et al, 2015 , Ferreira et al, 2020 ) drivers. Using a meta-analysis approach, Luiselli et al (2020) found no difference in the proportion of venomous snake species richness or abundance between tropical and temperate snake assemblages, and, conversely, not all poor rural populations are affected. Higher snakebite incidence observed in many tropical regions is therefore not simply a function of higher snake relative abundance or diversity or high rates of rural poverty, but rather the product of a range of factors acting at the local scale.…”
Section: Introductionmentioning
confidence: 84%
“…Snakebite incidence varies on a geographical and temporal scale, resulting from the interaction of anthropic ( Harrison et al, 2009 ; Mise et al, 2016 ) and environmental ( Chaves et al, 2015 , Ferreira et al, 2020 ) drivers. Using a meta-analysis approach, Luiselli et al (2020) found no difference in the proportion of venomous snake species richness or abundance between tropical and temperate snake assemblages, and, conversely, not all poor rural populations are affected. Higher snakebite incidence observed in many tropical regions is therefore not simply a function of higher snake relative abundance or diversity or high rates of rural poverty, but rather the product of a range of factors acting at the local scale.…”
Section: Introductionmentioning
confidence: 84%
“…( Gloydius himalayanus ) ( Warrell, 2003 ) or below 43° south ( Bothrops ammodytoides ) ( Carrasco et al, 2010 ). These characteristics of snake biodiversity result in high snakebite envenoming incidence in the warm tropics ( Yañez-Arenas et al, 2014 ), again as a result of higher venomous snake abundance ( Luiselli et al, 2020 ). Also, snakebite envenoming incidence is higher in the tropics because high climatic suitability allows snake populations to grow faster and achieve higher population densities ( Holt, 2020 ; Osorio-Olvera et al, 2019 ).…”
Section: Distributional Ecology Of Venomous Snakesmentioning
confidence: 99%
“…On the other, many snake species seem to be less sensitive to habitat-related anthropogenic disturbances in comparison to other species ( Suazo-Ortuño et al, 2008 ), probably because snakes have biological traits that make them less prone to extinction, such as larger clutches at larger body sizes compared to mammals because snake offspring size does not increase in proportion to size at reproductive maturity ( Reed, 2003 ). The snake species most affected by human activities and land use change have relatively narrow geographical distributions, feed on vertebrates (as opposed to molluscs or arthropods), and are aquatic ( Luiselli et al, 2020 ; Todd et al, 2017 ). Also, there is little evidence that the negative public perception of venomous snakes is a widespread extinction risk factor ( Todd et al, 2017 ), even though active persecution can in fact decrease snake populations ( Means, 2009 ).…”
Section: Distributional Ecology Of Venomous Snakesmentioning
confidence: 99%
See 2 more Smart Citations